Malaysian private university students’ perception of online discussion forums: A qualitative enquiry - Leow, Serena Wai Yee *; Lee, Cheng Ean Catherine * (UTM Press, 2020)
The continuous advancement in technology has transformed physical learning platforms into digital spaces in higher education. In Malaysia, instructors and students are gradually adopting the e-learning or blended-learning approach by using online discussion forums (e.g. BlackBoard) or social networking sites (e.g. Facebook groups) to engage students’ participation in courses and encourage self-directed learning. This study presents a qualitative view of students’ perception of engaging in online discussion forums in a synchronous learning environment, and their views on the positive and negative aspects of using online discussion forums for learning. Results indicate that students perceive autonomy and sense of belongingness in the online community as main factors that influence their voluntary and active participation in the online discussion forums. Technical challenges remain as a key factor in determining students’ interests to utilize online discussion forums for learning. While future research is needed to assess the sentiments of Malaysian students in online learning, this study was intended to provide Malaysian instructors and higher education institutions a preview on the sentiments of students towards online learning to better improve the aspects of technical, pedagogical methods and policies for online learning as the nation moves towards Education 4.0.